Vers une analyse des dimensions négatives de la proximité - Armelle Caron; André Torre (Développement Durable et Territoires)
This paper proposes a land-use conflicts analysis in terms of proximity. The first part of the paper presents the results of empirical studies on land-use and neighbourhood conflicts in the French countryside. Such study cases permit to underline the major part plays by the geographic proximity in the emergence of land use conflicts. The second part of the paper is devoted to the exploration and the characterisation of the geographic proximity "polemogene" properties. These latter are balanced with the virtues of organised proximity that may favoured the emergence of negotiated solutions to the conflicts. In the third part of the paper, an analysis chart that combines spatial and organisational dimensions of proximity is proposed. With such an analytical framework it is possible to identify the different types of land use and neighbourhood conflicts and to qualify some of their cooperative issues.